"Omics" in oral cancer: New approaches for biomarker discovery. (March 2018) - Rai, Vertika; Mukherjee, Rashmi; Ghosh, Ananta K.; Routray, Aurobinda; Chakraborty, Chandan
Highlights: The prognosis of oral cancer still remains poor in spite of advances in therapy. Early diagnosis of oral cancer remains the key to improved patient survival. "Omics" approach for screening of oral cancer is highlighted in this review. Biomarkers may be promising targets for future treatment modalities. Abstract: Objectives: In this review paper, we explored the application of " omics" approaches in the study of oral cancer (OC). It will provide a better understanding of how " omics" approaches may lead to novel biomarker molecules or molecular signatures with potential value in clinical practice. A future direction of " omics" -driven research in OC is also discussed. Methods: Studies on " omics "-based approaches [genomics/proteomics/transcriptomics/metabolomics] were investigated for differentiating oral squamous cell carcinoma, oral sub-mucous fibrosis, oral leukoplakia, oral lichen planus, oral erythroplakia from normal cases. Electronic databases viz., PubMed, Springer, and Google Scholar were searched. Results: One eighty-one studies were included in this review. The review shows that the fields of genomics, transcriptomics, proteomics, and metabolomics-based marker identification have implemented advanced tools to screen early changes in DNA, RNA, protein, and metabolite expression in OC population. Conclusions: It may be concluded that despite advances in OC therapy, symptomatic presentation occurs at an advanced stage, where various curative treatment options become very limited. A molecular level study is essential for detecting an OC biomarker at an early stage. Modern "Omics" strategies can potentially make a major contribution to meet this need.